Profiling hepatocellular carcinoma aggressiveness with contrast-enhanced ultrasound and gadoxetate disodium-enhanced MRI: An intra-individual comparative study based on the Liver Imaging Reporting and Data System. Issue 154 (September 2022) - Yang, Jie; Jiang, Hanyu; Xie, Kunlin; Bashir, Mustafa R.; Wan, Haifeng; Huang, Jiayan; Qin, Yun; Chen, Jie; Lu, Qiang; Song, Bin
Highlights: Marked discrepancies were found between contrast-enhanced ultrasound (CEUS) and gadoxetate disodium-enhanced MRI (EOB-MRI) in evaluating LI-RADS features and categories, especially for LR-TIV and LR-M. Compared with EOB-MRI, CEUS showed superior diagnostic specificity for macrovascular invasion at pathology. LR-M features on EOB-MRI provided more information regarding tumor grade and MVI status in HCC patients than CEUS. Abstract: Purpose: Contrast-enhanced ultrasound (CEUS) and gadoxetate disodium-enhanced MRI (EOB-MRI) may synergize in profiling hepatocellular carcinoma (HCC) aggressiveness considering distinct imaging traits. This study aimed to intra-individually compare CEUS and EOB-MRI with Liver Imaging Reporting and Data System (LI-RADS) in assessing HCC aggressiveness. Method: From January 2015 to November 2020, consecutive at-risk patients with surgically-confirmed HCC who underwent both preoperative CEUS and EOB-MRI examinations were retrospectively enrolled. Image analyses were conducted independently by two masked radiologists for CEUS and EOB-MRI, respectively. The diagnostic performance of each modality for macrovascular invasion against pathology was evaluated and compared with the McNemar's test, while Edmondson-Steiner grade and the presence of microvascular invasion (MVI) were compared between patients with and without LR-M features on each modality. Results: A total of 140 patients (mean age, 51.9 years ± 11.0; 116 men) were included. Inter-modality agreement was poor (κ = -0.087 ∼ 0.139) for major LI-RADS features and moderate (κ = 0.449) for overall LI-RADS categorization, and LR-TIV and LR-M were the top sources of inter-modality variations. Although CEUS demonstrated significantly higher specificity for diagnosing macrovascular invasion (96% vs. 89%, P  =.02), LR-M features on EOB-MRI were more effective in identifying higher Edmondson-Steiner grades ( P  =.01) and MVI ( P  =.02). Conclusions: Marked discrepancies were found between CEUS and EOB-MRI in evaluating LI-RADS features and categories. Whereas CEUS showed superior diagnostic specificity for macrovascular invasion, LR-M features on EOB-MRI provided more information regarding tumor grade and MVI status in HCC patients.